La catedral sin órganos. Elementos para la reconstrucción de una catedral a partir del arte moderno norteamericano. The cathedral without organs. Elements for the reconstruction of a cathedral from the american modern art - Ripollés Llauradó, Jaime (Arte, Individuo y Sociedad, 2005)
This article tries to go round a contemporary art museum: Dia:Beacon of New York, as if it were a medieval cathedral. Its shows the ressemblances and differences between several aesthetics proposals of the 60’s and 70’s associates to the minimalism, post minimalism, as Land Art, Pop Art, to the arquitectonic elements of a cathedral. We try to explain the transition from the traditional religious rite tothe phenomenon of modern art. This passage was the ground of the modern aesthetics for Walter Benjamin, as the first assumption of the artistics behaviours after war. If we make a reconstruction of the simbolic function of the objects found in a church we will be in the way of undestand the modern museum as a cathedral without organs.